PARTIAL MELTING EXPERIMENTS OF BIMINERALIC ECLOGITE AND THE ROLE OF RECYCLED MAFIC OCEANIC CRUST IN THE GENESIS OF OCEAN ISLAND BASALTS - Kogiso T.; Hirschmann M.M. (My University, 2006)
Bimineralic eclogite, which consists solely of garnet and clinopyroxene, is a likely component of some of the ancient recycled crust residing in basalt source regions. It may originate during subduction of altered mid-ocean ridge basalt (MORB) crust, owing to extraction of small degree partial melts or siliceous hydrous fluids. It may also originate by fractional removal of early-formed partial melts from recycled crust or from pyroxenite originating by other processes. We have performed high-pressure experiments on a bimineralic eclogite (B-ECL1) and its mixture with olivine (B-ECL1-OL) at 3 and 5 GPa. Degrees of melting are slightly higher for B-ECL1-OL than for B-ECL1 at given temperatures, suggesting that addition of small amounts of olivine enhances melt productivity of bimineralic eclogite. Solidus and liquidus temperatures of B-ECL1 are slightly higher than those of B-ECL1-OL and MORB-like pyroxenite, but are lower than those of high-MgO pyroxenite and peridotite, suggesting that bimineralic eclogite is not necessarily refractory compared to other likely mantle lithologies. Partial melts of B-ECL1 and B-ECL1-OL are nepheline-normative. Because garnet and clinopyroxene in these compositions partially melt at a eutectic-like minimum with a composition that is nepheline-normative, a wide range of bimineralic eclogite compositions, including that of subducted-crust origin, that consist of garnet and clinopyroxene with compositions similar to those of B-ECL1 can produce nepheline-normative (= alkali - basaltic) liquids. Thus, in contrast to the common assumption that partial melting of recycled oceanic crust produces silicic magmas, we conclude that such lithologies can produce nepheline-normative partial melts if they first experience fractional removal of fluids or melts. The partial melts from B-ECL1 are too low in MgO to be parental to many alkalic OIB, but have low Al2O3 and high FeO comparable to those of alkalic OIB, suggesting that bimineralic recycled crust is a potential source for a low-Al2O3 and high-FeO component that is necessary for the genesis of alkalic OIB. © 2006 Elsevier B.V. All rights reserved.
Keywords: ECLOGITE; EXPERIMENTAL PETROLOGY; OCEAN ISLAND BASALT; PARTIAL MELTING; PYROXENITE